Effect of bioprocessing and fractionation on the structural, textural and sensory properties of gluten-free faba bean pasta. (April 2016) - Rosa-Sibakov, Natalia; Heiniö, Raija-Liisa; Cassan, Denis; Holopainen-Mantila, Ulla; Micard, Valérie; Lantto, Raija; Sozer, Nesli
Abstract: This work evaluated the effects of processing faba bean flour on textural, structural and sensory properties of gluten-free pasta. Pasta was prepared using faba bean flour, starch-rich fraction of faba bean flour or faba bean flour fermented with lactic acid bacteria. The impact of cross-linking enzyme transglutaminase (TG) on the quality of faba pasta was also studied. The structure, cooking quality, starch digestibility, textural and sensory characteristics of faba pasta samples were evaluated and compared to semolina pasta. Pasta prepared with faba bean and fermented faba bean flours had higher cooking loss (10.8–11.5%) and lower water absorption (130–160%) than semolina pasta (6 and 193%), but pasta prepared from fractionated faba flour had similar water absorption to semolina pasta. The texture of pasta made with faba bean flour was comparable to that of semolina pasta. Fermentation adversely affected the texture by increasing hardness, chewiness, sourness and flavour intensity. Starch hydrolysis index of pasta prepared with the three faba bean flours was similar to semolina pasta (46–50). TG reduced the in vitro starch hydrolysis index and increased some textural parameters of pasta made with faba bean flour, but no influence was observed on pasta made with fractionated or fermented faba. Highlights: Gluten-free pasta made from bioprocessed faba bean flour and its fractions. Faba bean pasta had lower cooking quality than semolina pasta, but similar texture. In vitro starch digestibility of faba bean pasta was similar to the semolina pasta. Cross-linking enzyme further decreased the in vitro starch digestibility.